Analisa Pengaruh Pemasangan Reflector Aluminium Foil pada PLTS Off-Grid dengan Panel PV 30 WP Polycrystalline pada Lampu Halaman Rumah - Syamsu Alfarizi (VISA: Journal of Vision and Ideas, 2025)
Today's life cannot be separated from electricity, starting from people living in villages and living in big cities. This underlies the use of solar power plants (PLTS) as a new renewable electricity source to replace fossil energy sources that have limited amounts and pollution that pollutes the environment. Solar cells (solar cells) as PLTS units have output power constraints that are not large enough and are very dependent on natural conditions. One method of optimizing solar cells is by using a reflector. Sunlight is a renewable energy source that can be used as a new power plant. But in the process certain additions to the solar cell module are needed so that the output voltage can be optimized. Efforts to optimize the electrical output of solar modules by maximizing the intensity of light falling on the surface of the solar module using an Aluminium foil. From 7 days of data collection, the results obtained showed that there was an increase in the output of the solar modules, for PV using Reflectors, an average power output of 18.9 watts was obtained, while PV panels without Reflectors obtained an average power of 16.7 watts, as a percentage. The resulting difference in power is 13%.